Are aquatic aerobic exercise programs effective in decreasing pain levels in patients with fibromyalgia?. Issue 1 (January 2018) - Danner, Christine; Freeman, Kathryn
Abstract : EVIDENCE‐BASED ANSWER : Aquatic aerobic exercise programs reduce pain scores by up to 33% compared with no exercise for patients with fibromyalgia; however, aquatic programs are no more effective at reducing pain than land‐based therapy (SOR: A, meta‐analysis of RCTs and 2 RCTs).